ANALISIS KANDUNGAN SERAT PANGAN, INDEKS GLIKEMIK DAN BEBAN GLIKEMIK PANGAN TRADISIONAL DADIH SUSU SAPI DENGAN PENAMBAHAN SIROP YAKON (Smallanthus sonchifolius) - Nurul A'daalah (2022)
Type 2 diabetes mellitus (DMT2) is a metabolic disease with a high prevalence in the world that caused by poor quality of food intake. Therefore, alternative functional foods are needed to improve glycemic control in T2DM patients. This study aims to formulate cow's milk curd product with the addition of yacon syrup as a source of fiber and low glycemic index and glycemic load. The research method was a one-factor completely randomized design (CRD) with three treatment levels. Data analysis of dietary fiber, glycemic index and glycemic load used the One Way ANOVA test and continued with the Duncans Multiple Range Test (DMRT), while the data analysis for organoleptic tests used the Kruskal Waalis test and the Mann Whitney follow-up test. The selected formulation was determined using the exponential comparison method (MPE). The results of this study showed that there was no effect of the amount of yacon syrup on dietary fiber (p = 0.114), glycemic index (p = 0.747) and glycemic load (0.733). The selected formulation is the F3 product with the addition of 30% syrup.